2022
DOI: 10.1108/yc-09-2021-1390
|View full text |Cite
|
Sign up to set email alerts
|

Investigating the antecedents of luxury brand loyalty for Gen Z consumers in India: a PLS-SEM approach

Abstract: Purpose This study aims to explore the antecedents related to luxury brand loyalty in the Indian Gen Z consumer segment. It obtains the connection between luxury brand attachment, luxury brand trust and luxury brand loyalty. The study also envisages how luxury brand trust plays a mediation role in strengthening the relationship between luxury brand attachment and luxury brand loyalty in the Indian Gen Z consumer segment. Design/methodology/approach The empirical investigation is based on the Indian Gen Z con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 105 publications
0
5
0
Order By: Relevance
“…Following the preliminary analyses, we assessed the structural model. To examine the research hypotheses, we used a PLS algorithm to estimate the path coefficients of the structural model and used the bootstrapping method to test their statistical significance (Ghosh and Bhattacharya, 2022; Hair et al , 2016). The results presented in Table 3 indicate that most of the direct hypotheses are supported, except for the effects of connectivity, consistency and personalization on customer engagement.…”
Section: Resultsmentioning
confidence: 99%
“…Following the preliminary analyses, we assessed the structural model. To examine the research hypotheses, we used a PLS algorithm to estimate the path coefficients of the structural model and used the bootstrapping method to test their statistical significance (Ghosh and Bhattacharya, 2022; Hair et al , 2016). The results presented in Table 3 indicate that most of the direct hypotheses are supported, except for the effects of connectivity, consistency and personalization on customer engagement.…”
Section: Resultsmentioning
confidence: 99%
“…Recently, a fiery challenge for apparel brands is that consumers may perceive sustainability disclosure efforts as greenwashing. By utilizing the S-O-R framework, several studies found credible sources and transparency had a positive impact on consumers' attachment and trust [37][38][39][40][41]. However, to the best of our knowledge, applying the S-O-R model, previous studies did not experiment with sustainable positioning based on different credible sources (such as social media influencers) and transparency as stimuli in dealing with consumers' greenwashing perception.…”
Section: Theoretical Framework: S-o-r Modelmentioning
confidence: 92%
“…Consumers explore their favorite brands with rich consumption experiences and form brand loyalty. A study on the consumer group of Generation Z in the context of emerging economies confirmed that luxury brand trust had a significant impact on brand loyalty, which contributed to gaining insights into consumers in segmented markets [ 29 ]. In addition, successful product design has a positive cognitive and emotional response on consumers.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Product names, logos, and other related information, eye-catching colors, images that draw consumers' interest, and font styles that are closely related to brand image can usually attract consumers' attention [ 41 ]. To cultivate consumer loyalty towards a brand, establishing an attachment relationship alone is insufficient, it is imperative for consumers to concurrently develop trust in the brand [ 29 ].。Extensive research has investigated external information and helped establish trust in the brand [ 42 ]. Brand image is of significant importance in the brand promotion process.…”
Section: Hypotheses Developmentmentioning
confidence: 99%